Effectiveness Assessment of Tax Incentives - SIMONOVA, NATALYA YURIEVNA; AN, YULIA NIKOLAEVNA; IVANOVA, ELENA VLADIMIROVNA; MARKOV, SERGEY NIKOLAEVICH; MAKOVETSKY, MIKHAIL YURIEVICH (The journal of contemporary issues in business and government, 2021)
The article examines the role and importance of taxes for the formation of the budget system, highlights the shortcomings of the tax collection system, considers approaches to defining the concept of tax administration, assessing its effectiveness. The existing problems in terms of calculating the efficiency of tax administration have been identified. An assessment method was developed and tested on the example of several tax authorities in the Russian Federation. The study aims to develop theoretical aspects and methodology for assessing tax administration in the Russian Federation as the basis for ensuring budget revenues.